A case study of a dcm column-supported embankment over soft clay. Issue 3 (16th March 2022) - Liyanapathirana, D.S.
ABSTRACT: This paper investigates a case study of a highway embankment in Thailand constructed over Deep Cement Mixed (DCM) column improved ground. The case study was simulated using a 2D plane-strain model adopting the equivalent area approach for columns. Field measurements for deformations and excess pore pressures are compared with the finite element results to verify the numerical model, and to understand the load transfer mechanism. The most likely failure mode of the embankment was investigated by computing the Factors of Safety (FOS) against the bearing failure and bending failure of individual DCM columns, and the overall stability of the embankment. Results show that the most likely failure mode for this embankment is the bending failure of attached columns underneath side slopes. In the case study, attached columns are used to control the lateral deformations. In the paper, three other approaches used in practice for lateral deformation control are investigated: (i) Load transfer platform (LTP) with a geosynthetic layer above DCM columns with single columns near the side slopes (ii) T-shaped single columns near the side slopes and (iii) Reinforced single columns near the side slopes. Results show that in this particular case, due to the presence of a relatively deep fill layer above the soft clay deposit, lateral deformation control measures applied closer to the column heads such as LTP or T-shaped columns are not effective. However, the use of double columns with increased bending stiffness throughout the soft clay layer or increasing the length of columns underneath the embankment is the most effective solution in reducing lateral deformations.